2017
DOI: 10.5152/tjar.2017.98624
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term and Long-Term Effects of Dexamethasone on Cognitive Dysfunction Induced by Sevoflurane in Adult Rats

Abstract: Objective: Postoperative cognitive dysfunction (POCD) is common after anaesthesia in elderly patients. However, it may appear in patients of all ages. The main pathogenesis of cognitive dysfunction remains unclear, although there is some evidence that brain inflammation may alter cognitive abilities. In the present study, we aim to evaluate short-term and long-term effects of dexamethasone on cognitive dysfunction induced by sevoflurane anaesthesia in adult rats.Methods: Seven-month-old 30 male Wistar albino r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…30 On the other hand, the elevated antioxidant defence and apoptosis status were also observed in blood samples of sevoflurane-administered children. 8,32 Ye and his colleague reported that honokiol could alleviate surgery/ F I G U R E 7 Cistanche inhibits the oxidative stress induced by sevoflurane in a PPAR-γ-dependent manner. 8,32 Ye and his colleague reported that honokiol could alleviate surgery/ F I G U R E 7 Cistanche inhibits the oxidative stress induced by sevoflurane in a PPAR-γ-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 On the other hand, the elevated antioxidant defence and apoptosis status were also observed in blood samples of sevoflurane-administered children. 8,32 Ye and his colleague reported that honokiol could alleviate surgery/ F I G U R E 7 Cistanche inhibits the oxidative stress induced by sevoflurane in a PPAR-γ-dependent manner. 8,32 Ye and his colleague reported that honokiol could alleviate surgery/ F I G U R E 7 Cistanche inhibits the oxidative stress induced by sevoflurane in a PPAR-γ-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Detection limits were 8.0 pg/mL for IL-1β, 8.0 pg/mL for TNF-α and 4.0 pg/mL for IL-6. Hippocampal tissues were dissected on ice immediately and homogenized in saline by ultrasonic.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 98%
See 2 more Smart Citations
“…Sevoflurane may impair spatial learning and short-term and long-term memories in adult rats. 29 In severe to profound sudden deafness refractory to conventional ST, the daily perfusion of 4 mg/ml DEX through an intratympanic catheter is an easy, well accepted procedure that enables patients to receive a drug in the middle ear in a repeatable or sustained form, with minimal discomfort and a partial rescue (67.86%) and a speech recognition gain of 39% as suggested by Zanetti et al…”
Section: Miscellaneous Role Of Dexamethasonementioning
confidence: 99%